2018
DOI: 10.3390/ijerph15102285
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Blood Transfusion Units in Determining the Probability of Mortality among Elderly Trauma Patients Based on the Geriatric Trauma Outcome Scoring System: A Cross-Sectional Analysis Based on Trauma Registered Data

Abstract: Background: For elderly trauma patients, a prognostic tool called the Geriatric Trauma Outcome Score (GTOS), where GTOS = (age) + (ISS × 2.5) + (22 if any packed red blood cells (pRBCs) were transfused within 24 h after admission), was developed for predicting mortality. In such calculation, a score of 22 was added in the calculation of GTOS regardless of the transfused units of blood. This study aimed to assess the effect of transfused blood units on the mortality outcomes of the elderly trauma patients who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…As a result, the risk of adverse outcomes may be underestimated by the GTOS, especially for patients who require massive transfusions. 15 However, in our study, the predicted risks of morbidity and mortality by GTOS were not significantly different from the observed frequencies ( Figures 4 and 5 ).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…As a result, the risk of adverse outcomes may be underestimated by the GTOS, especially for patients who require massive transfusions. 15 However, in our study, the predicted risks of morbidity and mortality by GTOS were not significantly different from the observed frequencies ( Figures 4 and 5 ).…”
Section: Discussioncontrasting
confidence: 66%
“…It has been reported that a massive transfusion is associated with various adverse complications and that the units of red blood cells matter when determining the probability of mortality. 15 , 16 Massive amounts of blood transfusion can lead to a variety of serious complications, such as coagulation dysfunction, immunosuppression, respiratory system damage, hypothermia, and infection. 17 In the calculation of GTOS, the influence of the blood transfusion unit on body function was ignored while adding a score of 22 regardless of the blood unit transfused.…”
Section: Discussionmentioning
confidence: 99%
“…SI was suggested as an accurate tool for identifying early hypovolemic shock, severity of illness, and prognosis, especially in vascular injuries, hemorrhagic events, or trauma patients [ 20 , 21 , 22 , 23 , 24 , 25 ]. SI was also found to be an independent risk factor and a fast guide for the need of massive transfusion after trauma [ 25 , 26 , 27 ], and increased blood transfusion is regarded as an independent risk factor correlating with poor prognosis in trauma patients because of the alteration of cytokine levels and inflammatory processes caused by the transfused blood products [ 20 , 28 ]. Jonas et al concluded that an SI of greater than 0.9 predicts the necessity of intervention for hemostasis with high specificity (93.6%), and by lowering the threshold to ≥0.8, sensitivity is increased to 76.1% [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,28,30,31 Age is one predictor of mortality that has been topic of interest in prior MT studies, with results suggesting older patients had higher mortality rates for a given volume of blood. [39][40][41] Guerrero et al 40 demonstrated that patients aged >65 years old receiving ≥5 units of blood had a statistically significant increased risk of mortality, and also noted that plasma transfusion increased mortality 3-fold. Wu et al 41 analyzed the effects of the number of transfused blood units on mortality outcomes in elderly trauma patients and demonstrated as patients received more units of RBC, the higher their risk of mortality when compared to their younger counterparts.…”
Section: Discussionmentioning
confidence: 99%